Applying the networking power of Web 2.0 to the foreign language classroom: a taxonomy of the online peer interaction process. Issue 8 (2nd November 2018) - Peeters, Ward
ABSTRACT: Over the years, educational institutions have increasingly integrated Web 2.0 platforms as support tools in the foreign language learning curriculum to facilitate learners' engagement with the foreign language, increase motivation, and enable them to socially and collaboratively interact with fellow learners online. While descriptive studies on the topic have long dominated the field, they often lack close examinations of the nature of peer interaction, its mediating factors, and the effect it has on participants' learning curve. Presenting a research project in which two groups of more than 200 first-year foreign language majors were introduced to collaborative writing through Facebook, this study demonstrates how and why online peer interaction occurs and unfolds. It is shown that learners engage in cognitive and metacognitive processes while being social and responsible participants in the learning process. These findings are compiled in a taxonomy, modelling the communicative functions of peer interaction for academic purposes in the Facebook environment. This study illustrates how first-year English majors use language to establish themselves as learners in a new learning environment while discussing academic writing challenges online. In the peer interaction process, learners initiate cardinal learning activities in which they strive for proper cognitive, metacognitive, organisational and social functioning..